PROCESSES OF FOREARC AND ACCRETIONARY COMPLEX FORMATION DURING ARC-CONTINENT COLLISION IN THE SOUTHERN URAL MOUNTAINS - Brown D.; Spadea P. (My University, 1999)
The southern Ural Mountains of Russia contain a well-preserved, well-exposed Paleozoic accretionary wedge and forearc that can be readily compared to those in active arc-continent collision zones. The early convergent history in the southern Ural Mountains is marked by the generation of boninite-bearing arc tholeiites in the Magnitogorsk forearc, followed by arc tholeiite to calc-alkaline volcanism. With the entry of the East European craton continental crust in the subduction zone, volcanism waned and stopped, and high-pressure metamorphism of its leading edge took place. The arrival of the full thickness of the continental crust at the subduction zone is marked by increased sedimentation in the forearc basin and deposition of arc-derived volcaniclastic turbidites across the subducting slab. These, together with offscraped continental material, the exhumed high-pressure rocks, and a lherzolite massif, formed an accretionary wedge. A broad melange zone containing ultramafic fragments separates the forearc basement from the accretionary wedge, and marks the damage zone that developed along the backstop region. Shallow-water carbonates deposited unconformably on top of the mildly deformed arc record the end of the collision and the collapse of the arc.
Keywords: Paleozoic; Paleozoic; Палеозой